Sudden circulatory collapse caused by mechanical obstruction of the left main coronary trunk with infective endocarditis vegetation: a case report - Rena Usui; Masato Mutsuga; Yuji Narita; Yoshiyuki Tokuda; Sachie Terazawa; Hideki Ito; Wataru Uchida; Akihiko Usui (Surgical Case Reports, 2021)
Abstract Background Acute coronary syndrome (ACS) caused by mechanical obstruction of the coronary artery with a vegetation is extremely rare but associated with high mortality. The optimal management strategy of this condition remains controversial because of its scarcity. We experienced a case of sudden circulatory collapse due to mechanical occlusion of the left main coronary trunk with a vegetation. Case presentation A 68-year-old woman with aortic and mitral valve infective endocarditis suffered sudden dyspnea followed by heart arrest while awaiting surgery. Despite treatment with adequate antibiotic therapy, she had had multiple embolic infarctions and ruptured infectious cerebral aneurysms. We conducted transcatheter arterial embolization of the aneurysm and postponed the cardiac surgery due to residual aneurysmal blood flow. She suffered sudden cardiac arrest, and extracorporeal membrane oxygenation was applied after cardiopulmonary resuscitation. An echocardiogram revealed diffuse severe hypokinesis, and emergency coronary angiography was performed under suspicion of ACS. It revealed obstruction of the left main coronary trunk by a vegetation. Emergent cardiac surgery was performed. A vegetation had occluded the left coronary orifice. Aortic and mitral valve replacement with coronary artery bypass to the left antero-descending branch was performed. Regarding her cardiac function, she still required extracorporeal membrane oxygenation after surgery. She passed away 19 days after surgery due to multiple organ failure. Conclusions ACS caused by mechanical obstruction of the coronary artery with a vegetation is rare but associated with high mortality. When circulatory collapse acutely occurs in patients with aortic valve infective endocarditis, we should suspect acute coronary artery obstruction. Urgent coronary angiography is mandatory to rescue the patient while preparing for emergency surgery.